Speaking Back: Queerness, Temporality, and the Irish Voice in America - DOYLE, GAVIN (Trinity College Dublin. School of English. Discipline of English, 2019)
This thesis examines the intersections of Irishness and queerness in the work of five contemporary American writers and cultural figures. The queer Irish voice in America remains almost entirely neglected in Irish and Irish-American scholarship. This thesis provides the first comprehensive exploration of that heretofore obscured representation in order to fill this critical gap. The 1990s introduced explicitly for the first time the complexities of gay, lesbian, and queer Irish identity at America's largest display of cultural ethnic and national belonging: the St Patrick's Day parade. The conflicts between Irish queer groups and the parade organisers in New York and Boston, while emerging from the alleged impossibility of Irish queerness, have, conversely, ensured that an intimate connection between these two identifications endures in the public imaginary. Discussing the work of five writers, namely Alice McDermott, James McCourt, Peggy Shaw, Eileen Myles, and Stephanie Grant, this thesis considers the ways in which Irishness and queerness both collaborate and clash in the construction of Irish-American identity. The thesis argues against the mutual trends in Irish-American and gay and lesbian cultural, social, and historical discourses that centralise 'progressive' narratives in terms of socio-economic and legal advances. In so doing, the thesis privileges the bilateral backward glance in the queer scholarship of Heather Love, José Esteban Muñoz, Elizabeth Freeman, Benjamin Kahan, Jack Halberstam, Judith Butler, and, among others, David L. Eng, as well as in the critical interventions of Irish and Irish-American critics who challenge the truncated 'success' story of the Irish in America. Applying intersecting discourses of feminism, queer studies, psychoanalysis, and critical race studies, this thesis foregrounds feeling backward both as an attachment to negative feeling and as a critical shift in queer and Irish-American historiography. The authors in this thesis speak back to an oppressive present by feeling backward toward the past as a means through which to trace alternative routes for the future.
APPROVED
Keywords: Irish-American Literature; Queer Theory; Gender and Sexuality